Serum Levels of Irisin and Omentin-1 in Breast Neoplasms and Their Association with Tumor Histology - Grigorios Panagiotou; Sofia Triantafyllidou; Basil C. Tarlatzis; Eleni Papakonstantinou (International Journal of Endocrinology)
Breast cancer is associated with obesity, possibly due to direct effects of adipokines and myokines, such as omentin-1 and irisin. In this study, we aimed to evaluate omentin-1 and irisin levels in women with benign and/or malignant breast neoplasms vs. healthy controls. Disease-free individuals (N = 56) and patients with histologically proven benign (N = 61) or malignant tumor (N = 96; subdivided into recently diagnosed/treatment-naïve (N = 72) and chemotherapy-treated (N = 24) subgroups) were enrolled in this study. Demographic, biochemical, and tumor histological characteristics were recorded. Body composition parameters were assessed using bioelectrical impedance. Serum irisin and omentin-1 levels were quantified with ELISA kits. In adjusted models, irisin levels were higher in both benign and malignant cases compared to controls but were comparable between neoplasms. Further adjustment for omentin-1 levels showed that age (odds ratio (OR) = 1.05, 95% confidence interval (95% CI) = (1.02, 1.08), p<0.01) and irisin levels (OR = 5.30, 95% CI = (1.24, 22.38), p=0.03) were independent predictors of the presence of malignancy. These molecules were associated with each other and with other anthropometric and demographic parameters. Irisin was associated with tumor histological characteristics including Ki67% levels, Elston-Ellis grading system, and estrogen receptors status. Omentin-1 was also associated with the Elston-Ellis grading system. In conclusion, serum irisin is increased in patients with both benign and malignant diseases of the breast. When combined with omentin-1, irisin concentration was associated with the presence of breast malignancy. This molecule’s role as a potential diagnostic and/or prognostic agent in breast malignancies warrants further investigation in larger prospective studies.